Rough weather - Parker, Robert B., 1932-2010 (A Spenser mystery, 2009)
Heidi Bradshaw is wealthy, beautiful, and well-connected. She's also a notorious gold digger only recently separated from her latest husband - and she's hired Spenser to act as her stand-in spouse.The Boston P.I. is to accompany Heidi to her private island to attend her daughter's wedding. It should be a straightforward job, but when his old nemesis Rugar - the Gray Man - arrives, Spenser realizes that something is amiss. As a storm strikes, cutting off the island, a kidnapping and a series of murders turn celebrations into chaos.With six dead bodies and more questions than he can handle, Spenser begins a search for answers - and the Gray Man.